2022
DOI: 10.3354/meps14040
|View full text |Cite|
|
Sign up to set email alerts
|

Larger females have more calves: influence of maternal body length on fecundity in North Atlantic right whales

Abstract: North Atlantic right whales (NARW) are critically endangered and have been declining in abundance since 2011. In the past decade, human-caused mortalities from vessel strikes and entanglements have been increasing, while birth rates in the population are at a 40 yr low. In addition to declining abundance, recent studies have shown that NARW length-at-age is decreasing due to the energetic impacts of sub-lethal entanglements, and that the body condition of the population is poorer than closely related southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…We found that calves' TLs were positively related to their mothers' TLs, meaning longer calves were associated with longer mothers (Figure 5). This same trend was observed in humpback whales in Eastern and Western Australia (Christiansen et al, 2016;Russel et al, 2022), as well as in Eastern North Pacific gray whales (Christiansen et al, 2021) and southern and North Atlantic right whales (Best and Rüther, 1992;Christiansen et al, 2018;Stewart et al, 2022). In general, longer body lengths are associated with increased calf survivorship, as well as increased reproductive success in baleen whales (Pack et al, 2009;Stewart et al, 2022).…”
Section: Body Size Of Mother-calf Pairssupporting
confidence: 64%
See 1 more Smart Citation
“…We found that calves' TLs were positively related to their mothers' TLs, meaning longer calves were associated with longer mothers (Figure 5). This same trend was observed in humpback whales in Eastern and Western Australia (Christiansen et al, 2016;Russel et al, 2022), as well as in Eastern North Pacific gray whales (Christiansen et al, 2021) and southern and North Atlantic right whales (Best and Rüther, 1992;Christiansen et al, 2018;Stewart et al, 2022). In general, longer body lengths are associated with increased calf survivorship, as well as increased reproductive success in baleen whales (Pack et al, 2009;Stewart et al, 2022).…”
Section: Body Size Of Mother-calf Pairssupporting
confidence: 64%
“…Photogrammetry from unoccupied aircraft systems (UAS, UAVs, or drones) is an effective non-invasive tool for obtaining measurements of cetaceans in remote environments (Durban et al, 2015). UAS have been used to measure body condition in blue (Balaenoptera musculus), gray (Eschrichtius robustus), and northern (Eubalaena glacialis) and southern right whales (Eubalaena australis) (Christiansen et al, 2016;Durban et al, 2016;Christiansen et al, 2018;Lemos et al, 2020;Christiansen et al, 2021;Stewart et al, 2022;Torres et al, 2022). For humpback whales, studies have described trends in body condition along the migration routes (Christiansen et al, 2020b;Russell et al, 2022), the North Atlantic feeding grounds (Aoki et al, 2021), and the Western Australian breeding grounds (Christiansen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study found evidence of stunted growth in young right whales (<10 years old) that were observed with attached gear or whose mothers had attached gear or severe entanglement injuries while nursing (Stewart et al, 2021) indicating an additional sub‐lethal effect. This stunted growth effect has also impacted the reproductive output of females (Stewart et al 2022). Here we apply another tool—photographic evidence of health—to assess how entanglements are affecting right whale health.…”
Section: Introductionmentioning
confidence: 99%
“…Energy budgets are also affected by variability in the distribution and availability of their copepod prey (primarily Calanus finmarchicus ), which has been linked with female reproductive success (Meyer‐Gutbrod et al 2015). Likely as a result of energetic effects, total body lengths have decreased over time (Stewart et al 2021), which further impacts reproductive output (Stewart et al 2022). Whales are also exposed to anthropogenic noise (Hatch et al 2012), chemical pollutants and biotoxins (Doucette et al 2012), which can compromise health (e.g.…”
Section: Introductionmentioning
confidence: 99%